Quantum gauge boson propagators in the light front - Suzuki, A. T. [UNESP]; Sales, J. H O (World Scientific Publishing, 2004)
Gauge fields in the light front are traditionally addressed via, the employment of an algebraic condition n·A = 0 in the Lagrangian density, where Aμ is the gauge field (Abelian or non-Abelian) and nμ is the external, light-like, constant vector which defines the gauge proper. However, this condition though necessary is not sufficient to fix the gauge completely; there still remains a residual gauge freedom that must be addressed appropriately. To do this, we need to define the condition (n·A) (∂·A) = 0 with n·A = 0 = ∂·A. The implementation of this condition in the theory gives rise to a gauge boson propagator (in momentum space) leading to conspicuous nonlocal singularities of the type (k·n)-α where α = 1, 2. These singularities must be conveniently treated, and by convenient we mean not only mathemathically well-defined but physically sound and meaningful as well. In calculating such a propagator for one and two noncovariant gauge bosons those singularities demand from the outset the use of a prescription such as the Mandelstam-Leibbrandt (ML) one. We show that the implementation of the ML prescription does not remove certain pathologies associated with zero modes. However we present a causal, singularity-softening prescription and show how to keep causality from being broken without the zero mode nuisance and letting only the propagation of physical degrees of freedom.
Keywords: Light front; Quantum gauge bosons; Singularities in Feynman propagators; boson; calculation; density; electric field; hardness; light; mathematics; quantum chemistry; sound; space; theory